Education extends working life : gender-specific effects of education at the transition to retirement - Seegers, Marco [Verfasser] (My University, 2021)
"In July 2021, the Federal Employment Agency published an announcement stating that more than one million employees are now aged over 67.* Employment at an older age is becoming increasingly normal, albeit for different reasons. It is revealed that older women are particularly likely to have a lower income. It is also more probable that they will be affected by poverty. The present article investigates how gender-specific life histories structure the transition to retirement and looks at the influence exerted by level of education." (author's abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.3.1 Bildungsangebot & -nachfrage; 370; Erwerbstätigkeit; Bildungsniveau; Bildungsabschluss; Berufsausstieg; Rentenalter; Männer; Frauen; Nationales Bildungspanel